KOREAN NAMES IN SCREEN TRANSLATION:TRANSLITERATION ISSUES IN UKRAINIAN ADAPTATIONS (BULLETIN OF TARAS SHEVCHENKO NATIONAL UNIVERSITY OF KYIV. ORIENTAL LANGUAGES AND LITERATURES, 2025)
Background. This article addresses the problem of rendering Korean personal names in Ukrainian audiovisual translation, with a particular focus on the adaptation of TV series available on the streaming platform Netflix. The study reviews the main systems of Korean romanization and transliteration, identifies common errors in the rendering of names, examines the influence of cultural and linguistic factors on translation decisions, and suggests ways to improve the practice of name translation. The research combines linguistic and cultural approaches, emphasizing the importance of preserving the authenticity of names during adaptation for Ukrainian-speaking audiences in accordance with the norms of the Ukrainian language.Methods. The research employed three principal methods: the descriptive method, which enabled the systematization of the phonetic and structural features of Korean personal names; the comparative method, which facilitated the identification of recurrent tendencies and errors in Ukrainian translations; and the linguacultural method, which made it possible to account for the cultural context and to analyze its impact on the perception of characters by Ukrainian audiences.Results. The research reveals a lack of a unified and standardized system for the transliteration of Korean names in Ukrainian audiovisual translation. This results in variability, phonetic distortions, and translation errors in the rendering of character names. The analysis of specific cases demonstrates both technical and cultural-semantic distortions. These findings highlight the urgent need for the development of a consistent, Ukraine-oriented transliteration system that ensures accurate and stable rendering of Korean names in localized media products.Сonclusions. The study confirms that the accurate rendering of Korean personal names is an essential component of high-quality audiovisual translation. Despite the availability of various transliteration systems (both Latin- and Cyrillic-based, such as the McCune–Reischauer system, the Revised Romanization of Korean, the Yale system, and the systems developed by O. Kholodovych and L. Kontsevych), Ukrainian translators still tend to make errors by applying one or even several systems simultaneously. This highlights the relevance of further research into Korean phonetics and phonology. The scientific value of the study lies in the systematization of approaches to the transliteration of Korean names and the identification of major problems that complicate their adequate rendering in Ukrainian translations. The findings may serve as a basis for developing a unified methodology and for further research in translation studies and Korean linguistics. The practical value consists in the applicability of the results to translation practice, particularly in the work of localizers, dubbing studios, and subtitling professionals. The recommendations put forward in this study can contribute to improving the quality of Ukrainian localization of Korean audiovisual products and to ensuring both accuracy and authenticity in the rendering of proper names. It is hoped that the outcomes of future research will provide the foundation for the creation of a new Ukrainian system of transliteration and transcription that will preserve the unique features of the Korean language and render them as closely as possible within the norms of Ukrainian.
Keywords: Korean language; cinematic discourse; film translation; literary translation; adaptation; transliteration; transcription; proper names; personal names